2023
DOI: 10.1002/fft2.199
|View full text |Cite
|
Sign up to set email alerts
|

New hints for improving sleep: Tea polyphenols mediate gut microbiota to regulate circadian disturbances

Abstract: Biological rhythm is a natural physiological phenomenon of the human body, which is regulated by the biological rhythm system, including the sleep cycle, body temperature fluctuation, endocrine level, biological metabolism, and so on. Sleep disturbance is one of the main manifestations of circadian biological rhythm disorder, which has a serious impact on people's work and quality of life. Studies have shown that gut microbiota and circadian rhythms can interact through the brain-gut pathway. Tea polyphenols c… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
4
0

Year Published

2023
2023
2025
2025

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 10 publications
(4 citation statements)
references
References 122 publications
0
4
0
Order By: Relevance
“…Sleep has a more profound effect on the latter [58,105,106]. A large number of reports have verified that SD has the ability to cause alterations in glucose tolerance, acute insulin response to glucose, glucose effectiveness, and insulin sensitivity, all presenting a trend of decrease [30,58,106]. The mechanisms linking SD and abnormal glucose metabolism lie in several aspects: (1) the activation of the sympathetic nervous system can lower β-cells responses to glucose, thus resulting in reduced insulin sensitivity; (2) increasing free fatty acids brought by SD via promoting gluconeogenesis can lead to insulin resistance and hyperglycemia; and (3) the inflammation caused by SD, as mentioned above, can lead to insulin resistance, mainly via cytokines and corresponding signaling pathways (TNF-α & IKKβ/NF-κB pathway, IL-6 & JAK-STAT pathway) [107,108].…”
Section: Metabolic Diseasesmentioning
confidence: 99%
See 1 more Smart Citation
“…Sleep has a more profound effect on the latter [58,105,106]. A large number of reports have verified that SD has the ability to cause alterations in glucose tolerance, acute insulin response to glucose, glucose effectiveness, and insulin sensitivity, all presenting a trend of decrease [30,58,106]. The mechanisms linking SD and abnormal glucose metabolism lie in several aspects: (1) the activation of the sympathetic nervous system can lower β-cells responses to glucose, thus resulting in reduced insulin sensitivity; (2) increasing free fatty acids brought by SD via promoting gluconeogenesis can lead to insulin resistance and hyperglycemia; and (3) the inflammation caused by SD, as mentioned above, can lead to insulin resistance, mainly via cytokines and corresponding signaling pathways (TNF-α & IKKβ/NF-κB pathway, IL-6 & JAK-STAT pathway) [107,108].…”
Section: Metabolic Diseasesmentioning
confidence: 99%
“…Previous research has found that 20% to one-quarter of the population of the United States is forced to face it [16][17][18] because of improper diet [19], pressure [20,21], and increasing brain stimulation by smartphones [1]. Possible adverse outcomes elicited by SD include depression (in a bidirectional relationship with SD) [22][23][24][25][26], obesity [27,28], diabetes [14,29], cardiovascular disease [30,31], cancer [32,33], neurological dysfunction [31,34], and even death [34]. Therefore, a better understanding of the association between SD and human diseases, as well as the underlying mechanisms of action, is of critical importance.…”
Section: Introductionmentioning
confidence: 99%
“…PCoA, NMDS, and heatmap clustering analyses clearly demonstrated distinct characteristics of the gut bacterial community of loaches under the two feeding conditions on day 10. This divergence in microbial composition may be attributed to the abundance of digestive enzymes and symbiotic microorganisms within the gut, whereas TPs are prone to metabolic transformations facilitated by these enzymes or microorganisms [51]. The metabolism of TPs by the gut microbiota involves multiple pathways, leading to the production of diverse metabolites with distinct structures, such as pyrogallol, 5-(3 ′ ,4 ′dihydroxyphenyl)-, or 5-(3 ′ ,4 ′ ,5 ′ -trihydroxyphenyl)-γ-valerolactone.…”
Section: Discussionmentioning
confidence: 99%
“…Catechins are a class of flavan-3-ol, along with flavonols, flavanones, flavanonols, leucoanthocyanidins (flavan-3,4-diols) and anthocyanidins, belong to the class of flavonoids, a complex class of phenolic substances ( Braicu et al, 2013 ; Sagar N A et al, 2022 ). Accounting for about 60%–80% on the total tea polyphenols, catechins are important functional components in tea and possess various bioactivities, such as antioxidant, anti-inflammatory, anti-microbial antiviral and immunomodulatory effects ( Anandh Babu and Liu, 2008 ; Maheshwari S et al, 2022 ; Xiang et al, 2023 ). Catechins mainly consist of catechin (C), epicatechin (EC), gallocatechin (GC), epigallocatechin (EGC), catechin gallate (CG), epicatechin gallate (ECG), gallocatechin gallate (GCG) and epigallocatechin gallate (EGCG).…”
Section: Introductionmentioning
confidence: 99%